Representasi Model 3D Artefak Menggunakan Metode Structure From Motion Berbasis Fotogrametri Di Museum Ranggawarsita Semarang - zaman, Badroe; Rachmawati, Eka Putri; Asmiatun, Siti (The Indonesian Journal of Computer Science, 2024)
The development of the digital creative industry is growing very rapidly, utilizing information technology as an option, one of which is three-dimensional (3D) representation technology. 3D representation technology drives innovation in various sectors such as virtual reality, filmmaking, video games, geospatial surveying, architecture, and archaeology. 3D modeling of historical objects has gained attention in recent years. 3D model representation of artifacts is an attempt at digital documentation in case the object is damaged. One of the methods in 3D model representation is by using the photogrammetry-based Structure from Motion (SfM) method. The photogrammetry-based Structure from Motion (SfM) method is a stage of creating 3D models from several artifact images captured by a smartphone camera and then processed into 3D objects from a software. Objects in the form of photos in this study were taken directly from several shooting viewpoints in the Ranggawarsita museum. The results of the 3D model in this study can be utilized as digital assets for various purposes such as educational media for historical objects.